Engineered nanomaterials and crops: physiology and growth of barley as affected by nanoscale cerium oxide - Mattiello, Alessandro; Pošćić, Filip; Fellet, Guido; Zavalloni, Costanza; Fontana, Marta; Piani, Barbara; Vischi, Massimo; Miceli, Fabiano; Musetti, Rita; Marchiol, Luca (Italian Journal of Agronomy, 2016)
In recent years, remarkable progress has been made in developing nanotechnology. This has led to a fast-growth of commercial applications, which involve the use of a great variety of manufactured nanomaterials. Given that, soils and sediments are the ultimate sinks of engineered nanomaterials (ENMs), they can be taken up by microorganisms, nematodes, earthworms or plants, and potentially transferred to the food chain up to animals and humans. However, the reactions of the biota exposed to ENMs of different size are still not well understood. Very few studies on nanoparticles-plant interactions have been published, so far. In this paper we report the results of multiple experiments carried out to study the effects of cerium oxide nanoparticles (nCeO2) on Hordeum vulgare. The nCeO2 powder and suspension were characterised for specific surface area, z-average size, and zeta potential. Germinating caryopses and barley seedlings were exposed to an aqueous dispersion of nCeO2 at respectively 0, 500, 1000 and 2000 mg L–1. Data on root elongation, mitotic index and cerium concentration in seedlings were collected. Plants of barley were grown to physiological maturity in soil enriched with respectively 500 and 1000 mg kg–1 of nCeO2. We reported that seed germination was not affected by the nCeO2, however, signals of genotoxicity were evidenced by mitotic index coupled with a shortage of root elongation. In the life-cycle experiment although no toxicity symptoms were detected, we demonstrated that barley growth was affected by nCeO2.